HISTORI PEMBERLAKUAN PERADILAN AGAMA ERA KERAJAAN ISLAM DAN PENJAJAHAN DI INDONESIA - Faisal (Al-Qadha, 2019)
The journey of the Religious Courts that has been passed in such a long period oftime means that we are talking about the past, namely the history of the Religious Courts.With the entry of Islam into Indonesia, which for the first time in the first century Hijri (1 H /7 AD) brought directly from Arabia by merchants from Mecca and Medina, the communitybegan to implement the teachings and rules of Islamic religion in everyday life. The ReligiousCourt is one of the Special Courts under the authority of the Supreme Court as the highestcourt in the Republic of Indonesia. As an Islamic Judiciary that had been established longbefore Indonesia's independence, the Religious Courts certainly could not be separated fromthe changes that occurred considering the reign of the Government of Indonesia had been heldby various people with different backgrounds, politics and goals, surely it would have animpact on the existence Religious Courts both materially and immaterially, including duringthe Dutch and Japanese colonial rule in Indonesia.